Privacy Concerns in Personalized Advertising Effectiveness on Social Media - Lia Febria Lina; Adhy Setiyanto (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
Social media is considered to be one of the greatest environments in which users interact with each other. This is also used by marketers in promoting their products to target consumers it commonly called personalized advertising. Various studies related to personalized advertising have inconsistency result. This study aims to fill the gaps with examining personalized advertising on the perceived advertising value of consumers that affect purchase intention and examine the role of consumer privacy concerns as a moderating variable. This study uses a survey method on 131 respondents who are active users of Instagram in Indonesia. The findings show that the more advertisements are adjusted to the user's interests, purchase history, interests, the more advertisements provide a level of benefit that makes users have purchase intention. Furthermore, privacy concerns weaken effect personalized advertising and advertising value. Further research suggestions are also discussed in this study.